Effect of different treatments on ovarian condition and relative variationof steroids and insulin-like growth factor I in serum during induction of oestrus of seasonally acyclic sheep - VLCKOVA, R; SOPKOVÎ‘, D; VALOCKÝ, I; POŠIVÁK, J (The Indian Journal of Animal Sciences, 2012)
Hormonal treatment during the non-breeding season is effective at precise synchronization of oestrus for fixed time insemination with the ability to increase ovulation rate in ewes. Three methods of assisted oestrus in Vallachian ewes were studied during the non-breeding season – group A: control, groups B, C: application of 20 mg flugestone acetate impregnated intravaginal sponges for 12 days + 1000 IU/500 IU equine chorionic gonadotrophin, respectively, on day of sponge withdrawal, group D/ovsynch protocol (day –9: lecirelinum 0.0125 mg/head, day –3: cloprostenolum 0.0375 mg/head, day -1: lecirelinum 0.0125 mg/head), n=6 for each. Laparotomy was carried out on ewes of all groups 24 h after the last treatment. Ovaries were collected, measured, and their volume was calculated, surface follicles were counted and measured, too. Blood was collected on the last day of treatment and on the day of laparotomy and progesterone (P4), oestradiol-17ß (E2), and insulin-like growth factor I (IGF-I) concentrations were analyzed in blood serums. E2 concentrations were significantly higher on day of laparotomy in groups A and C. P4 and IGF-I concentrations did not vary between or among groups. Volumes of the ovaries were significantly higher in control group when compared to groups B and D. Not a single treatment affected number or size of the follicles on the ovaries of Vallachian sheep positively, regardless the most effective treatment for assisted oestrous in the non-breeding season is found to be the use of progestogen vaginal sponges with 1000 IU eCG which may increase the ovulation rate.